Strategi Manajemen Resiko UntukMeningkatkan Kinerja Organisasi - Yosi Angel Dirawati; Merika Setiawati (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
This study aims to analyze risk management strategies to improve organizational performance through a qualitative approach with case study methods. Organizations face various risks that can hinder the achievement of strategic goals and objectives. Effective risk management is essential to identify, assess, manage, and control potential events that may disrupt organizational  objectives.  This  research  examines  the  relationship  between  strategic  planning,  risk  management effectiveness, and organizational performance. The findings indicate that effective risk management can strengthen the relationship between strategy formulation and organizational performance. Organizations implementing systematic risk management  processes—including  context  establishment,  risk  identification,  risk  analysis,  risk  evaluation,  and  risk treatment—demonstrate better performance in achieving their objectives. Strategic planning combined with effective risk management enables organizations to be more systematic in management, focus on goal achievement efforts, and improve decision-making quality. This study concludes that integrating risk management into strategic planning is crucial for enhancing organizational competitiveness and sustainability in facing business uncertainties.